Method of Particular Solutions for Second-Order Differential Equation with Variable Coefficients via Orthogonal Polynomials - Huantian Xie; Zhaozhong Zhang; Ziwu Jiang; Jianwei Zhou (Journal of Function Spaces)
In this paper, with classic Legendre polynomials, a method of particular solutions (MPS, for short) is proposed to solve a kind of second-order differential equations with a variable coefficient on a unit interval. The particular solutions, satisfying the natural Dirichlet boundary conditions, are constructed with orthogonal Legendre polynomials for the variable coefficient case. Meanwhile, we investigate the a-priori error estimates of the MPS approximations. Two a-priori error estimations in H1- and L∞-norms are shown to depict the convergence order of numerical approximations, respectively. Some numerical examples and convergence rates are provided to validate the merits of our proposed meshless method.